PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DIMEDIASI OLEH DISIPLIN KERJA PADA DINAS PENCEGAH DAN PEMADAM KEBAKARAN KOTA MEDAN (PIONIR: JURNAL PENDIDIKAN, 2021)
The purpose of this study was to determine the effect of leadership and work motivation on employee performance mediated by work discipline at the Medan City Fire Department and Prevention Service. Quantitative associative methodology is used in this research. All employees of the Medan City Fire Prevention and Service Office became the population in this study. The sample used was 50 respondents. Questionnaires and interviews that have been tested for validity and reliability are the data collection techniques used. The data analysis used in this study were: (1) Analysis of the measurement model analysis (outer model), (2) Structural model analysis (inner model), and (3) Single test path analysis). The results showed that (1) the influence of leadership on employee performance was positive and significant with a value of 0.267, (2) the effect of work motivation on employee performance was positive and significant with a value of 0.259, (3) the influence of leadership on employee work discipline was positive and significant. with a value of 0.933, (4) the effect of work motivation on employee work discipline is positive and significant with a value of 0.027, (5) the effect of work discipline on employee performance is positive and significant with a value of 0.052, (6) the influence of leadership on employee performance through work discipline positively and significantly with a value of 0.048, meaning that work discipline acts as an intervening variable (mediator), and (7) the effect of work motivation on performance through work discipline is positive and significant with a value of 0.011 which means that work discipline acts as an intervening variable (mediator).
Keywords: Leadership; Work Motivation; Work Discipline; and Employee Performance